Exploring the concept of pain of Australian children with and without pain: qualitative study - Joshua W Pate; Tim Noblet; Julia M Hush; Mark J. Hancock; Renee Sandells; Meg Pounder; Verity Pacey (BMJ Open)
Objective A person’s concept of pain can be defined as how they understand what pain actually is, what function it serves and what biological processes are thought to underpin it. This study aimed to explore the concept of pain in children with and without persistent pain.Design In-depth, face-to-face interviews with drawing tasks were conducted with 16 children (aged 8–12 years) in New South Wales, Australia. Thematic analysis was used to analyse and synthesise the data.Setting Children with persistent pain were identified from a pain clinic waiting list in Australia, and children without pain were identified through advertising flyers and email bulletins at a university and hospital.Participants Eight children had persistent pain and eight children were pain free.Results Four themes emerged from the data: ‘my pain-related knowledge’, ‘pain in the world around me’, ‘pain in me’ and ‘communicating my concept of pain’. A conceptual framework of the potential interactions between the themes resulting from the analysis is proposed. The concept of pain of Australian children aged 8–12 years varied depending on their knowledge, experiences and literacy levels. For example, when undertaking a drawing task, children with persistent pain tended to draw emotional elements to describe pain, whereas children who were pain free did not.Conclusions Gaining an in-depth understanding of a child’s previous pain-related experiences and knowledge is important to facilitate clear and meaningful pain science education. The use of age-appropriate language, in combination with appropriate assessment and education tasks such as drawing and discussing vignettes, allowed children to communicate their individual concept of pain.